Affecting Cognition and Quality of Life via Aerobic Exercise in Alzheimer's Disease. (January 2013) - Yu, Fang; Nelson, Nathaniel W.; Savik, Kay; Wyman, Jean F.; Dysken, Maurice; Bronas, Ulf G.
Aerobic exercise is a promising behavioral therapy for Alzheimer's disease (AD), yet few studies have investigated the effect of aerobic exercise on cognition in AD. The purpose of this pilot study was to examine the effect of 6-month aerobic exercise on the change in executive function, global cognition, quality of life (QOL), and depression in community-dwelling older adults with mild to moderate AD. A single group, repeated measures design with outcomes measured at baseline, 3 months, and 6 months was used. Results show that there were no significant changes in any measures except for depression ( p = .026). There was a trend toward improvement in executive function and QOL with moderate effect sizes (ESs) and a trend toward deterioration in global cognition with moderate to large ESs. Randomized controlled trials are needed to evaluate the therapeutic effect of aerobic exercise in older adults with AD.